HUBUNGAN FAKTOR KOMORBIDITAS, INTENSIFIKASI TERAPI, DAN PENGENDALIAN TEKANAN DARAH - Rita Suhadi; Jarir Atthobari; Bambang Irawan; Iwan Dwiprahasto (Sanata Dharma University, 2013)
Abstract: Background: Therapy intensification (TI) is the most important factor in bloodpressure control among the adherent patients. The TI is the physician prescription behavior toadd the item(s) and/or the dosage of hypertensive medicine when the patients' BP was ?10mmHgabove the target. Comorbid patients have 10mmHg lower BP target. Aims: to evaluate the effectof comorbidity on TI score and blood pressure control; and to correlate the variables of TI and BPcontrol. Method: retrospective cohort study done in 4 hospitals in Yogyakarta for 5 months. Thesubjects of age 18 years, hypertensive out-patient covered with Askes insurance, and ?1 visitwith uncontrolled BP were included. Hemodialysis subjects were excluded. Subjects weregrouped into with/without comorbid. The BP profile was analyzed with T-test, repeatedmeasurement Anova, and odds ratio. Results: subjects consisted of without (WO) (n=268) vs.with comorbid (W) (n=401) patients. Comorbid subjects had older age, more male proportionand more visits (p0.05). The profiles of final SBP/DBP in WO vs. W subjects were as follow:148.9/89.1 (WO) vs. 143.8/86.1mmHg (W) (p0.05); TI score (-) 0.360.26 (WO) vs. (-)0.380.24 (W) (p0.05); the final SBP: worse BP control 20.9 (WO) vs.16.2% (W), notcontrolled in all visits 38.1 vs. 45.9%, improved 17.5 vs. 23.9%, and good controlled in all visit23.5 vs.13.2%; proportion of subjects reached BP target 40.7% (WO) vs. 37.4% (W) (p0.05);the different of final minus target SBP: (-)9.018.5 vs. (-)13.917.4mmHg (p0.05); correlationbetween TI and variables of SBP (p0.05) with the coefficient (r) at 0.4-0.6 (medium).Conclusion: comorbidity had no effect on TI score; but subjects with comorbid had worse BPcontrol (p0.05); TI score correlated in medium level with SBP.Keywords: Comorbidity Factor, Therapy Intensification, Blood Pressure Control